Padrão de supervisão da enfermeira em Hospitais de Feira de Santana - BA - Leite, Maria Lucia Servo (1995)
This an exploratory descriptive study about Nurse Supervision Pattern (N.S.P.), achievcd in Feira de Santana-Bahia-Brazil, in 1T)4, which objcctivcs were to describe supervision pattern and to idcntify its factors of intcrfcrcncc. The population was nurses working ín hospital arca. The 'lool was a qucstionnaire, Descnptive slatistic was utdizcd (o Ireatmení of data. After interprelation and analysis of results, it. conclued; supervision pattern utilize d by nurse is not sys te matize d, being emphirical (planning isn'l systematic; thc íechmques and tools are utilized in a fragmented and dísjointed way. being conciso (o thc executo ion of routine (asks and cvaluíition isrft systcmalizeJ). showing an unpreparcdness of nurse to excrcisc thc fuction and failurc in lhe plax miíng of nursing service at all leveis, proving lack of perception of supervision while process. Statistically proved that kind of hospital is a factor that inlerfers at N.S.P. Ba.sed on literature. percentual exarn of results and authors profissional experíctice, it asserts that sex, academic forma tion. remuneralíon, Health political, planning and teaçhnic administrativo strueture are co nd i t i o na I factors of N.S.P,, as wcI! as lack of profcssional aulonomy. interfcrence oí\partisan políticaI, de í i c i e nc y of material and human recourses. low remuncration, unsuitable cnvircnimcnt and un satisfactorv intcrper.sonal relations, mentioned by subjecls.